Persistent Organic Pollutants and Mercury in Genetically Identified Inner Estuary Bottlenose Dolphin (Tursiops truncatus) Residents of the Guayaquil Gulf, Ecuador: Ecotoxicological Science in Support of Pollutant Management and Cetacean Conservation - Alava, Juan José; Calle, Paola; Tirapé, Ana; Biedenbach, George; Cadena, Omar Alvarado; Maruya, Keith; Lao, Wenjian; Aguirre, Windsor; Jiménez, Pedro J.; Domínguez, Gustavo A.; Bossart, Gregory D.; Fair, Patricia A. (Frontiers in Marine Science, 2020)
The bottlenose dolphin is the most common cetacean found in the coastal waters, estuaries and mangroves of Ecuador. However, its population size is gradually declining in the Gulf of Guayaquil, and anthropogenic factors including habitat degradation, uncontrolled dolphin watching, dredging activities, increasing maritime traffic, underwater noise, bycatch and marine pollution have been implicated in the decline. Very little is known concerning contamination by persistent organic pollutants (POPs) and mercury in bottlenose dolphins from the Pacific coast of South America. To address this research gap, the first assessment of total mercury (THg) and POPs, including polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), and polybrominated diphenyl ethers (PBDEs), in free-ranging bottlenose dolphins in mangroves (El Morro Mangrove Wildlife Refuge) of the Gulf of Guayaquil, was conducted in Ecuador in 2018. Dolphin samples (i.e. skin and blubber; n = 9), were obtained using dart biopsy field methods for contaminant analysis. POP concentrations ranged 0.60-16.4 mg/kg lipid weight, while THg ranged from 1.40 to 4.0 mg/kg dry weight. The predominant POPs were OCPs (51% of ∑POP), followed by PCBs (44%) and PBDEs (5.5%); particularly, p,p’-DDE, the main DDT metabolite and a potent anti-androgenic, accounted by 44% of ∑POP, ranging 0.12 to~9.0 mg/kg lw, followed by PCB 153 (8.0%) and PCB 180 (5.0%). PBDE 47 accounted for 2.0% of ∑POP. While the POP concentrations are lower than those found in dolphins from many other regions of the world, some of the THg concentrations are within the concentration range found in dolphins from the southeastern coast of the USA. The ecotoxicological risk assessment showed that some of the sampled dolphin are exposed to immunotoxic and endocrine disruption effects by POPs and mercury. The low genetic diversity of this distinctive dolphin population, likely exhibiting genetic isolation and a unique evolutionary heritage, could be lost if the population continues to decline in the face of anthropogenic threats, including chemical pollution. Our finding shows that bottlenose dolphins in coastal Ecuador are exposed to environmental contaminants and can be used as sentinel species of ecosystem health to monitor pollution in the region to support ecotoxicological risk assessment and regional pollutant management.